CHANCES IN PEDAGOGY AND PSYCHOLOGY FOR FUTURE TEACHERS TO STRENGTHEN THEIR PROFESSIONAL PERSPECTIVES - Mamatkulov Akmal Akhmadaliyevich (Scholar Express Journal, 2022)
Both teachers and students agree that learning is a memorable part of life. Anyone who has attained professionalism in any sector will first receive training as a teacher. As a result, one of today's most urgent challenges is the need to teach competent and outstanding individuals in the field of pedagogy. The construction of pedagogical and psychological chances during the teacher-training process is specifically discussed by the author in this essay
Keywords: Educator; students; psychological process; professional adaptation